Asimetrías en el desarrollo de los territorios de Costa Rica - Shirley Benavides Vindas; María Leonela Artavia Jiménez (Atlantic Review of Economics (ARoEc), 2018)
– The article presents the results of the interregional analysis of Costa Rica 2011-2016, from the perspective of neo-structuralist economics, based on official sources. The objective is to reflect differences in the socio-economic development of the country, relating them to productive structures, together should promote the development of labor markets through learning processes, and therefore the territories. From the analysis of the regions, it is possible to identify notable differences between the Central Region of the country and the peripheral regions, in social, economic and educational variables. In the peripheral regions, poverty, unemployment and informality increase, as well as the flow of people migrating to the center. In addition, we found higher levels of labor force specialization, and a high concentration of productive activities in the center. All these are situations that must be taken into account from public policies in order to reduce the asymmetries in the development of the Costa Rican territories. For this, the articulation between social, business and institutional actors is of great importance, as is an educational policy that responds to the needs of the territories.
Keywords: D63; H32; I32; I38; L1O15; O17; O18; 330; Development of territories; public politics; regional asymmetries; neo-structuralism; center-periphery relationship